Emerging roles of growth factors in osteonecrosis of the femoral head - Che, Zhenjia; Song, Yang; Zhu, Liwei; Liu, Tengyue; Li, Xudong; Huang, Lanfeng (Frontiers in Genetics, 2022)
Osteonecrosis of the femoral head (ONFH) is a potentially disabling orthopedic condition that requires total hip arthroplasty in most late-stage cases. However, mechanisms underlying the development of ONFH remain unknown, and the therapeutic strategies remain limited. Growth factors play a crucial role in different physiological processes, including cell proliferation, invasion, metabolism, apoptosis, and stem cell differentiation. Recent studies have reported that polymorphisms of growth factor-related genes are involved in the pathogenesis of ONFH. Tissue and genetic engineering are attractive strategies for treating early-stage ONFH. In this review, we summarized dysregulated growth factor-related genes and their role in the occurrence and development of ONFH. In addition, we discussed their potential clinical applications in tissue and genetic engineering for the treatment of ONFH.